2023
DOI: 10.1007/s00426-023-01834-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving children’s ability to remember intentions: a literature review on strategies to improve prospective memory during childhood

Abstract: Children often fail to remember executing intentions because prospective memory (PM) does not completely develop until late adolescence or young adulthood. PM failures are often observed in children and can have negative consequences on their everyday lives. Thus, in the last 50 years, various strategies to support children’s PM have been designed and evaluated, such as prompting children to use different encoding modalities, such as verbal, visual, and enacted modalities, or encoding strategies, such as imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…In this habitual PM context, we also examined the influence of cue visibility. Previous research in children indicated that having a visual reminder of the intention improves PM performance [ 14 , 24 ]. Interestingly, after 8 instances of retrieving the intention in Experiment 1, removing the box from participant’s line of sight had no effect on performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this habitual PM context, we also examined the influence of cue visibility. Previous research in children indicated that having a visual reminder of the intention improves PM performance [ 14 , 24 ]. Interestingly, after 8 instances of retrieving the intention in Experiment 1, removing the box from participant’s line of sight had no effect on performance.…”
Section: Discussionmentioning
confidence: 99%
“…This model predicts that individuals with poor EF will show poor PM performance, and that PM performance should improve as EF develops. While development in other domains are also relevant to PM performance (see Cottini [ 14 ] for a review), the majority of research with children has focused on how cognitive resource demands and availability affect performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation